Franciscan St. Michael’s Monastery of Rakvere, Estonia: Notes on Building History - Tamm, Jaan (Hikuin, 1997)
In late spring 1989 the leaders of what was then the Rakvere district commissioned Agu, an enterprise affiliated to the Estonian Heritage Society, to carry out archaeological investigation of an area to the east of the Rakvere house of culture on Theater Hill. The reason for the excavations was the district leadership’s wish to build a new house of culture at the site. Already the first excavations in summer 1989 revealed, and continued excavations in 1990 corroborated, the existence on the site of former settlement extending from the late Iron Age to the 19th century. Direct proof of it was a layer of midden 3.5 metres thick containing remains of an Iron Age settlement, foundations of the east and south wings of a medieval monastic complex and remains of later (17th-19th century) manorial buildings.